Improving survival of acute-on-chronic liver failure patients complicated with invasive pulmonary aspergillosis - Jie Gao (Nature Portfolio, 2018)
Abstract The mortality of acute-on-chronic liver failure (ACLF) patients complicated with invasive pulmonary aspergillosis (IPA) was extremely high. We aimed to explore prognostic value of the Chronic Liver Failure-Sequential Organ Failure Assessment (CLIF-SOFA) lung score and to establish an optimal voriconazole regimen for ACLF patients complicated with IPA. We retrospectively screened hospitalized ACLF patients in our hospital from July 2011 to April 2016, from which 20 probable IPA cases were diagnosed. Along with onsets of IPA, deteriorated diseases severity, especially lung conditions were found in those 20 ACLF patients. It was found that IPA patients with CLIF-SOFA lung score <2 had better 28-day survival than those with lung score >1 (11/13 vs 0/7, p < 0.001). Based on plasma voriconazole concentration measurement, an optimal voriconazole regimen (loading doses: 0.2 g twice daily; maintenance doses, 0.1 g once daily) was established, which resulted in rational trough plasma drug concentrations (1–5 μg/mL), good clinical outcomes (90-day survival rate of 6/8) and no observed adverse events. In conclusion, CLIF-SOFA lung score >1 was able to identify ACLF patients complicated with IPA encountering much higher 28-day mortality. An optimal voriconazole regimen was safe and effective in our ACLF patients complicated with IPA.